2013
DOI: 10.1038/ijos.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Periodontopathogen profile of healthy and oral lichen planus patients with gingivitis or periodontitis

Abstract: Oral lichen planus (OLP) is a chronic inflammatory disease that is frequently detected in oral tissues. The aim of our study was to identify the prevalence of the detection of periodontopathogenic microorganisms (Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia and Treponema denticola in OLP patients and to compare with this prevalence of periodontopathogenic microorganisms in healthy non-OLP patients. Our study included 27 (18 chronic periodontitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 44 publications
(56 reference statements)
2
26
0
Order By: Relevance
“…As the implementation of our sample collection had excluded those subjects with periodontal inflammation or other oral diseases, we could assume that the abundance shift of Porphyromonas had something to do with OLP state. Our findings supported the results of a previous study, in which higher periodontopathogens’ percentages were detected in OLP groups than those in the non-OLP groups 27 . This periodontopathogenic genus with high percentage may also play an important role in the etiology of OLP.…”
Section: Discussionsupporting
confidence: 92%
“…As the implementation of our sample collection had excluded those subjects with periodontal inflammation or other oral diseases, we could assume that the abundance shift of Porphyromonas had something to do with OLP state. Our findings supported the results of a previous study, in which higher periodontopathogens’ percentages were detected in OLP groups than those in the non-OLP groups 27 . This periodontopathogenic genus with high percentage may also play an important role in the etiology of OLP.…”
Section: Discussionsupporting
confidence: 92%
“…[ 33 ] Recently, it has been found in some literature that few periodontopathogenic microorganisms are also associated with the patients of OLP. [ 34 ] Role of candida infection is controversial in OLP. Several studies have shown an increased prevalence of candida species.…”
Section: Etiologymentioning
confidence: 99%
“…Since these OLP patients were asymptomatic, the differences in microbial species and quantity found in OLP lesions are most likely due to OLP disease process but not patients' inadequate hygiene maintenance caused by soreness/discomfort from these OLP lesions. Although the clinical types (erosive or reticular) and presence or absence of symptoms were not specified, Ertugrul et al [11] also found that the proportion of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, and Treponema denticola in total bacteria were higher in subgingival plaque samples taken from subjects having periodontitis and OLP than those having periodontitis without OLP. The results of these studies suggest that there may be correlation between the microbe and OLP.…”
mentioning
confidence: 99%